2023
DOI: 10.3389/fcvm.2023.1103681
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low-density lipoprotein cholesterol and lipoprotein(a) on mid-term clinical outcomes following coronary artery bypass grafting: A secondary analysis of the DACAB trial

Abstract: PurposeThe objective was to evaluate the influence of low-density lipoprotein cholesterol (LDL-C) and lipoprotein(a) [Lp(a)] on clinical outcomes in patients undergoing coronary artery bypass grafting (CABG).MethodsThis is a secondary analysis of a 5-year follow-up of the DACAB trial (NCT02201771), in which 500 patients who underwent primary isolated CABG were randomized to three-antiplatelet therapy for 1 year after surgery. Of them, 459 patients were recruited in this secondary analysis. Baseline LDL-C and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, only few studies including limited numbers of patients undergoing CABG revealed inconsistent results. 12 , 13 , 14 , 15 The distribution and prognostic implication of lipoprotein(a) in patients undergoing CABG are still largely unknown. Furthermore, much less attention has been paid to evaluating the influence of lipoprotein(a) on patients undergoing CABG with different levels of LDL‐C and different graft materials, which may be possible treatment options in the absence of approved lipoprotein(a)‐lowering therapy.…”
mentioning
confidence: 99%
“…However, only few studies including limited numbers of patients undergoing CABG revealed inconsistent results. 12 , 13 , 14 , 15 The distribution and prognostic implication of lipoprotein(a) in patients undergoing CABG are still largely unknown. Furthermore, much less attention has been paid to evaluating the influence of lipoprotein(a) on patients undergoing CABG with different levels of LDL‐C and different graft materials, which may be possible treatment options in the absence of approved lipoprotein(a)‐lowering therapy.…”
mentioning
confidence: 99%